Mary Does Not Learn Anything New: Applying Kim’s Critique of Mental Causation to the Knowledge Argument and the Problem of Consciousness - Khayat, Adam (Stance: an international undergraduate philosophy journal, 2019)
Within the discourse surrounding mind-body interaction, mental causation is intimately associated with non-reductive physicalism. However, such a theory holds two opposing views: that all causal properties and relations can be explicated by physics and that special sciences have an explanatory role. Jaegwon Kim attempts to deconstruct this problematic contradiction by arguing that it is untenable for non-reductive physicalists to explain human behavior by appeal to mental properties. In combination, Kim’s critique of mental causation and the phenomenal concept strategy serves as an effectual response to the anti-physicalist stance enclosed within the Knowledge Argument and the Zombie Thought Experiment.